2011
DOI: 10.1017/s0305000911000031
|View full text |Cite
|
Sign up to set email alerts
|

Extended Statistical Learning as an account for slow vocabulary growth*

Abstract: Stokes (2010) compared the lexicons of English-speaking late talkers (LT) with those of their typically developing (TD) peers on neighborhood density (ND) and word frequency (WF) characteristics and suggested that LTs employed learning strategies that differed from those of their TD peers. This research sought to explore the cross-linguistic validity of this conclusion. The lexicons (production, not recognition) of 208 French-speaking two-year-old children were coded for ND and WF. Regression revealed that ND … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
70
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(81 citation statements)
references
References 39 publications
(111 reference statements)
10
70
1
Order By: Relevance
“…That is, as vocabulary size increased, neighborhood density decreased and word frequency increased. Those findings were replicated in French-speaking children (Stokes, Kern, & Dos Santos, 2012) and in Danish-speaking children (Stokes, Blese, Basbøll, & Lambertsen, 2012). …”
Section: The Emerging Lexicon Of Children With Normal Hearingmentioning
confidence: 67%
“…That is, as vocabulary size increased, neighborhood density decreased and word frequency increased. Those findings were replicated in French-speaking children (Stokes, Kern, & Dos Santos, 2012) and in Danish-speaking children (Stokes, Blese, Basbøll, & Lambertsen, 2012). …”
Section: The Emerging Lexicon Of Children With Normal Hearingmentioning
confidence: 67%
“…Stokes, Kern, et al (2012) proposed a theory of Extended Statistical Learning (ExSL) to account for the slowed vocabulary development of toddlers who are late to talk based on the observation that those children with smaller vocabularies produce words that sound like many other ambient words (i.e., differ from many other words by only a single phoneme; Stokes, 2010; Stokes, Kern, et al, 2012). That is, ExSL was proposed to account for findings related to neighborhood density.…”
Section: Extended Statistical Learningmentioning
confidence: 99%
“…Thus, the general argument put forth by Stokes, Kern, et al (2012) was that children with smaller vocabularies are slow to acquire the distributional regularities of language input that support lexical learning. They suggested that it is these children who are also slow to relax the constraints on lexical learning afforded by statistical learning strategies.…”
Section: Extended Statistical Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Storkel (2009, see also 2004) analyzed the timing of nouns’ appearance in children’s (aged 16–30 months) productive lexicons, based on the proportion of children of each age reported by their parents to have produced the nouns on the MacArthur-Bates CDI (Fenson et al, 1994). Short, high degree words were known by more children and acquired at an earlier age (but see Stokes, 2010; Stokes, Kern, & Dos Santos,2012), but the strength of the effect decreased steadily after age 2., This finding does not conclusively demonstrate a degree effect, as Storkel used a composite score of length and degree, but it yields some support for predicting a positive effect of degree here. There is also evidence for substantial variability in children’s sensitivity to degree (Maekawa & Storkel, 2006).…”
Section: Introductionmentioning
confidence: 99%